La paggeria: una scuola alla corte del principe - Vanni, Laura (Studi sulla Formazione/Open Journal of Education, 2013)
The text analyzes the organization of the “paggeria”: the school, in the modern age, welcomed the children of noble families, in the court, with the aim to teach good manners, in the service of the Lord and to the rules of cortigiania. In an appendix to the text shows the handwritten document, signed by Cosimo III de’ Medici, in 1670, alleging’ “Istruzione e Capitoli da osservarsi nell’educazione dei Signori Paggi rossi”, kept in the National Library of Florence.